PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MUATAN PEMBELAJARAN IPAS KELAS IV SDN MAMPANG PRAPATAN 02 PAGI - Alisha Putri Najla (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to improve the critical thinking skills of class IV students at SDN Mampang Prapatan 02 Pagi using a problem based learning model. The method used in this research is Classroom Action Research (PTK) using the Kemmis and McTaggart model which begins with planning stages, implementing actions and observations, and reflection. The research subjects in this study were 29 students at SD Negeri Mampang Prapatan 02 Pagi. The data collection techniques used are observation, tests, documentation and field notes. The research results showed that the achievement obtained in the evaluation test of students' critical thinking abilities in cycle I reached 58.62%, that is, they had not reached the desired target. In cycle II, it showed that students' critical thinking abilities increased to 89.65%. This research shows that the Problem Based Learning learning model can improve the critical thinking skills of class IV-B students at SDN Mampang Prapatan 02 Pagi.   Keywords: critical thinking, PBL, problem-based learning